Dexamethasone-Induced Myeloid-Derived Suppressor Cells Prolong Allo Cardiac Graft Survival through iNOS- and Glucocorticoid Receptor-Dependent Mechanism - Zhao, Yang; Shen, Xiao-Fei; Cao, Ke; Ding, Jie; Kang, Xing; Guan, Wen-xian; Ding, Yi-tao; Liu, Bao-rui; Du, Jun-Feng (Frontiers in Immunology, 2018)
How to induce immune tolerance without long-term need for immunosuppressive drugs has always been a central problem in solid organ transplantation. Modulating immunoregulatory cells represents a potential target to resolve this problem. Myeloid-derived suppressor cells (MDSCs) are novel key immuneregulatory cells in the context of tumor development or transplantation, and can be generated in vitro. However, none of current systems for in vitro differentiation of MDSCs have successfully achieved long-term immune tolerance. Herein, we combined Dexamethasone (Dex), which is a classic immune regulatory drug in the clinic, with common MDSCs inducing cytokine GM-CSF to generate MDSCs in vitro. Addition of Dex into GM-CSF system specifically increased the number of CD11b+ Gr-1int/low MDSCs with an enhanced immunosuppressive function in vitro. Adoptive transfer of these MDSCs significantly prolonged heart allograft survival and also favored the expansion of regulatory T cells in vivo. Mechanistic studies showed that inducing nitric oxide synthase (iNOS) signaling was required for MDSCs in the control of T-cell response and glucocorticoid receptor (GR) signaling played a critical role in the recruitment of transferred MDSCs into allograft through upregulating CXCR2 expression on MDSCs. Blockade of GR signaling with its specific inhibitor or genetic deletion of iNOS reversed the protective effect of Dex-induced MDSCs on allograft rejection. Together, our results indicated that co-application of Dex and GM-CSF may be a new and important strategy for the induction of potent MDSCs to achieve immune tolerance in organ transplantation.